2009
DOI: 10.1158/0008-5472.can-08-2530
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Sodium Potassium Adenosine Triphosphatase Pump Sensitizes Cancer Cells to Anoikis and Prevents Distant Tumor Formation

Abstract: Normal epithelial cells undergo apoptosis upon detachment from the extracellular matrix, a process termed ''anoikis.'' However, malignant epithelial cells with metastatic potential resist anoikis and can survive in an anchorage-independent fashion. Molecules that sensitize resistant cells to anoikis will be useful chemical probes to understand this pathway. To identify novel anoikis sensitizers in anoikis-resistant PPC-1 prostate adenocarcinoma cells, a library of 2,000 off-patent drugs and natural products wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
77
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 43 publications
2
77
1
1
Order By: Relevance
“…One previous study reported that ouabain at very high concentration (1 and 10 µM) showed antiproliferative results on 3 different prostate cancer cell lines [14]. A second study described the effects of ouabain (from 0.01 to 100µM) on viability on a small panel of cancer cell lines with essentially the same results [18]. Furthermore combination strategy seemed to be more successful in H295R cells, at least in cell viability and proliferation assay.…”
Section: Discussionmentioning
confidence: 90%
“…One previous study reported that ouabain at very high concentration (1 and 10 µM) showed antiproliferative results on 3 different prostate cancer cell lines [14]. A second study described the effects of ouabain (from 0.01 to 100µM) on viability on a small panel of cancer cell lines with essentially the same results [18]. Furthermore combination strategy seemed to be more successful in H295R cells, at least in cell viability and proliferation assay.…”
Section: Discussionmentioning
confidence: 90%
“…Recent findings that cancer biopsies express much higher levels of different sodium pump subunits might provide a rational basis for this increased sensitivity of cancer cells to the effects of these drugs. Several mechanisms have been proposed by us and others, to account for their cytotoxic action, including inhibition of HIF-1 synthesis (27), downregulation of c-MYC (28), inhibition of topoisomerase II (29), upregulation of death receptors DR4 and DR5 (30), increased expression of ROS (31), alterations in membrane fluidity (32) and anoikis induction (33). Moreover, Wang and colleagues, recently showed that digoxin and other cardiac glycosides inhibit p53 synthesis by a mechanism relieved by Sarcoma kinase (Src kinase) or mitogen-activated protein kinase (MAPK) inhibition, highlighting a potential benefit for the use of these drugs in human cancers with a gain of function p53 mutation (34).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9] The main reason was the expression of Na ϩ /K ϩ -ATPase in cancer cells was higher than that in normal cells, and provided more binding sites for CSs. Previous research has shown the Na ϩ /K ϩ -ATPase a1 subunit was highly expressed in malignant cells, including human prostate cancer PC-3, DU-145 cells, human non-small cell lung cancer (NSCLC) A549 cells, 10) glioblastomas Hs683, U373-MG, U87-MG, T98G cells, 11) and breast cancer MCF-7 cells.…”
mentioning
confidence: 99%